To belong or not to belong : variations autour du mythe associatif chez Virginia Woolf - Stéphanie Ravez (Cahiers Victoriens et Edouardiens)
Despite her personal and political involvement in many societies and circles, Virginia Woolf surprisingly displays a fairly ambivalent, if not critical, attitude towards them in her fiction. This is especially the case of a 1920 short-story, ‘A Society’, which tells about a society of women rebelling against the patriarchal order. Written in the same period, the autobiographical sketch ‘Old Bloomsbury’ goes back over the birth of the famous group of intellectuals to which the author’s name is closely connected. This article proposes to confront both texts and read them in the light of her celebrated feminist essays published in the thirties where she openly rejects the membership of any society or club.